DAMPAK LITERASI DIGITAL TERHADAP KEPROFESIONALAN GURU SEKOLAH MENENGAH ATAS : LITERATUR REVIEW - Ainia Asfiya’i; Alda Putri Macelly; Maftuh Fauji Dimyati; Eko Retno Mulyaningrum; Reni Rakhmawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
This literature review aims to determine the impact of digital literacy on increasing teacher professionalism inteaching and learning activities in biology learning in Indonesia. The method used in this research uses the literaturereview method to analyze teachers' professional competence in digital literacy. The data collection technique is bysearching for journals relevant to this topic via Google Scholar and Sinta 1 - 6 for the last 5 year period from 2020- 2024. The results of the article analysis show that; Digital literacy has an important impact on improving a teacher'sprofessionalism in teaching and learning activities. Digital literacy has a significant impact on improving teacherprofessionalism because it allows teachers to create digital learning media that are more productive and help thelearning process.